Komplementowanie w różnych kulturach: kontrastywna analiza komplementów i reakcji na nie w językach angielskim, polskim i rosyjskim = A Study of Compliments across Cultures: A Contrastive Analysis of Compliments and Compliments Responses in English, Polish and Russian - Kuzio, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
As positive speech acts, compliments and compliment responses seem to play an important role in daily verbal communication. Incorporating a questionnaire survey as well as pragmatic theories and sociolinguistic views of differences in language, this study investigated intercultural differences in compliments and compliment responses.
Keywords: komplement; komunikacja międzykulturowa; odpowiedź na komplement; compliment; intercultural communication; compliment response